The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5539/ijbm.v12n11p194
|View full text |Cite
|
Sign up to set email alerts
|

PLS-SEM Based Analysis of Service Quality and Satisfaction in Open Distance Learning in Sri Lanka

Abstract: Students' Perceived Service Quality (SPSQ) and Students' Satisfaction (SSAT) in Open Distance Learning (ODL) are renowned features in Higher Education (HE) field in the present-day. The vast number of research studies have addressed diverse types of variables on different grounds. The ODL students are from various family backgrounds such as cultural, social, technological skill levels, and most importantly defer from basic educational entry qualifications. This must cognize how the HE institutions are able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The current study using Fornell & Larcker criterion to measure discriminant validity. The square root of the AVE for each construct should be higher than the correlation with other latent variables (Perera et al, 2017). The other measure for discriminant validity used in this study is Heterotrait-Monotrait Ratio (HTMT), with suggested minimum extraction that should be below 1.0 (Ab Hamid, Sami, Sidek, 2017).…”
Section: Validity and Reliability Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study using Fornell & Larcker criterion to measure discriminant validity. The square root of the AVE for each construct should be higher than the correlation with other latent variables (Perera et al, 2017). The other measure for discriminant validity used in this study is Heterotrait-Monotrait Ratio (HTMT), with suggested minimum extraction that should be below 1.0 (Ab Hamid, Sami, Sidek, 2017).…”
Section: Validity and Reliability Resultsmentioning
confidence: 99%
“…In order to complete the analysis of the structural model, construct validity and reliability is conducted first in this study. As stated by another research (Perera, Johar, Kathibi, Atan, Abeysekera, Dharmaratne, 2017), the indicators which indicated the low-reliability score (Cronbach's Alpha and Composite Reliability <0.7) or AVE value (<0.50) were eliminated to support the validity evaluation. The eliminated indicators were PRI2, SR1, and SR2.…”
Section: Validity and Reliability Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing roles of advance technology in the learning field motivate researchers to understand the usefulness of such technologies in education framework. Computers, computer networks, projectors, smart boards as an example of such technologies are often employed in the form of e-learning to improve classroom activities (Bayrak & Akcam, 2017;Perera et al, 2017). All of these tools improve the student learning experience and enhance student engagement, in addition to improving the course administration and management all through the use of information and communication technologies (Tso, 2015).…”
Section: E-learning and Blended Learningmentioning
confidence: 99%
“…Evaluation of a service quality from the overall superiority of this service is the customer's perception of all assessments or attitudes related to service excellence (Perera et al, 2017). There are three-dimensional view of a quality of service that interaction, physical quality and the quality of the company (Quddus & Hudrasyah, 2014).…”
Section: Service Quality (Il)mentioning
confidence: 99%